2013
DOI: 10.1038/bjc.2013.389
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious BRCA1/2 mutation is an independent risk factor for carboplatin hypersensitivity reactions

Abstract: Background:We tested the hypothesis that BRCA1/2 mutation carriers with ovarian cancer are at higher risk of carboplatin hypersensitivity reactions (HSRs).Methods:Medical records of women enrolled in two carboplatin+olaparib clinical trials (NCT01237067/NCT01445418) were reviewed. A maximum of eight cycles containing carboplatin were administered.Results:All women (N=87) had good performance status and end-organ function. Incidences of carboplatin HSR before enrolment and on study were 17% and 21%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 30 publications
(37 reference statements)
1
58
2
2
Order By: Relevance
“…The average prevalence of this mutation in tubo-ovarian cancer population is 13 to 17% (3), but when considering only allergic patients to carboplatin enrolled in the RDD program we identified a prevalence of 34%. This corroborates the finding of the BRCA mutation as an independent risk factor for HSR to carboplatin (1), since its prevalence is notably increased in our population.…”
Section: To the Editorsupporting
confidence: 92%
See 2 more Smart Citations
“…The average prevalence of this mutation in tubo-ovarian cancer population is 13 to 17% (3), but when considering only allergic patients to carboplatin enrolled in the RDD program we identified a prevalence of 34%. This corroborates the finding of the BRCA mutation as an independent risk factor for HSR to carboplatin (1), since its prevalence is notably increased in our population.…”
Section: To the Editorsupporting
confidence: 92%
“…The studied population was composed of 87 patients with ovarian, fallopian tube or primary peritoneal cancer. This study also found that patients with BRCA1/2 mutations developed a HSR to carboplatin with a lower cumulative dose (1). …”
Section: To the Editormentioning
confidence: 63%
See 1 more Smart Citation
“…However, retreatment with platinum-based chemotherapy poses certain risks, including exacerbation of residual neuropathy from initial treatment, enhanced myelosuppression, or onset of hypersensitivity reactions to platinum. Moon and colleagues identified a higher frequency of platinum hypersensitivity reactions at a lower net exposure in g BRCA m patients (30). Use of the cediranib/olaparib combination in lieu of platinum-containing chemotherapy would potentially reduce this risk while prolonging the platinum-free interval.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the high dose of veliparib attained with cisplatin based therapy in this phase I study, myelosuppression has limited the dose of veliparib that can be combined with carboplatin as a single agent (50) or with carboplatin and paclitaxel doublet (51). Data from ovarian cancer literature demonstrate that patients with a BRCA1/2 mutation have increased susceptibility and shortened time to carboplatin hypersensitivity reactions, independent of other risk factors for hypersensitivity reactions (52). Therefore, cisplatin compared to carboplatin may improve the tolerability and durability of the platinum based combination regimens in BRCA mutation carriers in the metastatic setting where patients receive multiple cycles of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%